2015
DOI: 10.1111/cid.12311
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Healing at Calcium‐ versus Calcium Phosphate‐Modified Titanium Implant Surfaces: An Experimental Study in Dogs

Abstract: Moderately rough surfaces modified with calcium ions or discrete calcium phosphate nanocrystalline deposition showed similar patterns of sequential healing. Higher new bone percentages were found at BTI unicCa compared with the 3i T3 implants, the difference being statistically significant at 2 and 4 weeks observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 16 publications
1
25
0
1
Order By: Relevance
“…; Favero et al. , ), while a non‐submerged approach was used in the remaining three (Berglundh et al. and Abrahamsson et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Favero et al. , ), while a non‐submerged approach was used in the remaining three (Berglundh et al. and Abrahamsson et al.…”
Section: Methodsmentioning
confidence: 99%
“…; Favero et al. , ; Mainetti et al. , ) to evaluate the proportion of the various tissue components that occur on the surface during the early phases of osseointegration.…”
mentioning
confidence: 99%
“…Calcium ions at titanium oxide implant surfaces form a hydrated layer that has been reported to promote surface‐based provisional matrix formation, platelet activation, and osseointegration in vivo . As calcium ions are also responsible for the binding of several proteins, the presence of these ions may in turn increase the bacterial affinity for the surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[4] However, only a few report on the effects of free calcium ions, which can be readily released to the implant microenvironment. [5][6][7] A recent study of these two strategies in vivo and found statistically significant new bone formation at implants modified with free calcium ions compared with implants coated with a nanometric calcium phosphate deposition. [7] Calcium ions (Ca 2+ ) are centrally involved in a multitude of biological processes, among which the entire lifecycle of bone from formation to repair.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] A recent study of these two strategies in vivo and found statistically significant new bone formation at implants modified with free calcium ions compared with implants coated with a nanometric calcium phosphate deposition. [7] Calcium ions (Ca 2+ ) are centrally involved in a multitude of biological processes, among which the entire lifecycle of bone from formation to repair. [8][9][10][11] Indeed, Ca 2+ mediates platelet activation and provisional matrix formation, binds acidic-rich proteins and creates supersaturating conditions for bone-mineral nucleation.…”
Section: Introductionmentioning
confidence: 99%